On the extrinsic Hall-Petch to inverse Hall-Petch transition in nanocrystalline Ni-Co electrodeposits. (September 2022) - Kong, Jonathan; Haché, Michel J.R.; Tam, Jason; McCrea, Jonathan L.; Howe, Jane; Erb, Uwe
Abstract: The Hall-Petch to inverse Hall-Petch (HP-IHP) transition of an electrodeposited nanocrystalline Ni-32at%Co alloy was examined by annealing the as-plated alloy to obtain grain sizes ranging between 18 – 239 nm. We describe this transition as an extrinsic HP-IHP transition (extrinsic to the fabrication process) as opposed to the intrinsic HP-IHP transition observed in materials in their as-plated state (intrinsic to the fabrication process). The extrinsic transition of the Ni-32at%Co alloy took place in the mid-stage of abnormal grain growth, at an average grain size of ∼30 nm. Grain boundary relaxation governs the IHP region and maximum hardness was achieved at initial development of bimodal grain size; meanwhile late-stage abnormal grain growth and further normal grain growth led to the reduction in hardness in the HP region. Segregation of sulfur impurities to grain boundaries, crystallographic orientation and annealed twin development did not have significant contributions to the observed change in hardness. Graphical abstract: Image, graphical abstract